Análisis del uso del bambú como materia prima para sistema de riego - Peñarrieta Zambrano, Byron Antonio (2025)
This research aims to validate the use of bamboo as a raw material for implementing a drip irrigation system. Bamboo is a crucial species widely employed in construction and agricultural activities. Internationally, countries like China, Ghana, and India have implemented strategies to maximize bamboo usage due to its comparative advantages. Conversely, the widespread use of plastic products, particularly in agriculture, has resulted in environmental issues influencing water quality and soil health. This, in turn, negatively affects bacterial activity and long-term productivity. In this study, we consider that bamboo possesses the necessary technical characteristics to be implemented in a drip irrigation system as a sustainable and resilient material compared to conventional materials such as polyvinyl chloride.